Causal discourse structures in medical referral materials: a humanistic insight - Chinaguh, Emmanuel C.; Akeredolu-Ale, Bolanle I.; Adeosun, Kehinde G.; Adejumobi, Hannah O. (Linguistik Online, 2023)
Humanistic studies on medical causality from language studies have hardly explored how causality is constructed in medical referral materials, which is the research gap this study intends to fill. For data, forty completed National Health Insurance Authority (NHIA) medical referral forms, comprising 842 words and medical signs, were purposively selected from a healthcare provider in Abeokuta, Ogun State, Nigeria, and subjected to discourse analysis with insights from the causal coherence categories of Mann/Thompson’s (1987) Rhetorical Structure Theory. The paper identified two causal relations/structures – nonvolitional cause and nonvolitional result – in the data. Each structure reveals the primacy of diagnosis among the medical processes of diagnosing, investigating and treating or referring. The diagnosis proposition is primed as the consequence of pathophysiological causation in a diagnostic schema; while in the medical referral process, it is elevated as the causation for a medical referral, for instance for further specialist review and management, in a medical-referral schema. The construal of the semantic parameter of non-volition in the coherence relations is aided by the reality that illness is not intended, except caused by self-harm or suicide. The relations were signalled by four signal types, which are genre, semantic, syntactic, and semiotic; and six specific signals – mapping, lexical overlap, lexical chain, adverbials, semiotic overlap, and lexical-semiotic chain. These are implicit signals that complement the concise presentation of the medical processes. To conclude, this research provides the causal modeling of some medical processes, which highlights the prominence of diagnosis in medical referrals.